PEMBUATAN PERMEN JAMU CEKOK DAN KARAKTERISTIK YANG DIHASILKAN - Sri Hidayati; Fibra Nurainy; Dyah Kusumawardani; Miendiera Sefriadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Medicinal herbs are stimulants made from various types of medicinal plants which function to stimulate children's appetite. One of the drawbacks of herbal punching is that it is bitter in taste and the aroma is less favorable so that it takes effort to make herbal punching a preferred product, namely by processing the herbs into candy. The purpose of this study was to obtain the concentration of agar flour as a gelling agent for the best sensory and chemical properties of the herbal squeezed candy. The treatments were gelatin concentrations of 1%, 1.2%, 1.4%, 1.6%, 1.8% and 2%. The study used a Complete Randomized Block Design (CRBD) and further test of the Least Significant Difference. The results showed that the best agar concentration was 1.6% with candy products which had an aroma score of 3.73 (not typical of herbal medicine), a texture score of 4.16 (chewy), a taste score of 3.66 (sweet) and 80. % of children's panelists said they liked it. The herbal medicine jelly candy has water content of 12.61%, reducing sugar of 9.48, ash content of 8.96%. All meet SNI except ash content. Keywords: herbal punching, jelly candy,  jelly flour